A arte resiste à censura? reflexões contemporâneas - Oliveira, Deborah Moreira de; Targa, Thaynã Silva; Costa, Thays Alves (Revista do Colóquio, 2020)
This article aims to investigate censorship and prohibition cases in the art field, especially in the contemporaneity. Recently, we suffer attacks in the cultural and artistic field motivated by the idea of moral and religious extremism. Thus, we select cases in the national scope that involved works of art. This happened in productions like Queermuseu (2018) exposition - closed after a boycott and the propagation of fakenews about the works; Other production is the HQ Vingadores - A cruzada das Crianças by Marvel, exposed in the Bienal do Livro (2019) - which portraited a kiss from a homoaffective couple - that in January, the mayor Crivella requested censorship for believing that the content was improper for childs; So as the performance Freedom kick (2020) from the Indecline collective, that simulated a football game which the ball was the representation of the president Jair Bolsonaro head. The cases of intolerance and violence seems to grow in Brazil, including against the artistics expressions, therefore, our intention is to expose and reflects about it.